Tobacco Retailers Near Schools and the Violations of Tobacco Retailing Laws in Thailand. Issue 6 (November 2019) - Phetphum, Chakkraphan; Noosorn, Narongsak
Abstract : Context: A growing body of evidence indicates that the location of tobacco retailers may influence tobacco access among youths. Objective: The aim of this research was to examine the relationship between the proximity of tobacco retailers to schools and the violations of tobacco retailing laws. Design: A cross-sectional survey research. Main Outcome Measures: We applied geographical information system to measure the proximity between tobacco retailers and schools and linked them with self-report surveys concerning the violations of tobacco retailing laws. We then tested the relationship between the proximity of tobacco retailers within 500 m of schools and the violations of tobacco retailing laws by the χ 2 test. Participants: All tobacco retailers (121 shops) and schools (14 schools) (covering 5 levels: 2 primary schools, 6 primary-middle schools, 3 secondary schools, 2 vocational schools, and 1 university) in a town municipality in Thailand. Results: Most tobacco retailers were most densely located around primary schools and located less than 500 m away from schools (47.1%), and most of them had violated the tobacco retailing laws. In addition, it was found that the tobacco retailers that were located less than 500 m away from schools allowed customers to do a self-service ( P = .04). Nonetheless, the tobacco shops that were far away from schools, more than 500 m, were likely to sell the cigarettes in sticks ( P = .04). Conclusion: Our results suggest that Thai young people may be at a particularly high risk of tobacco-related problems due to high exposure to tobacco retailers and sales near their educational institutions. We support the possibility of zoning restrictions that can be used to prohibit the operation of tobacco retailers close to schools.